Migração internacional e lazer no litoral turístico potiguar - Salete Goncalves (2018)
This thesis sought to understand in which way it is processed the dynamics of international migration oriented by leisure in the eastern potiguar coast and what are its influence in the generation of new touristic and migratory flows in Rio Grande do Norte. For this purpose, it was pursued to investigate the profile, the trajectory and the decisive factors in the residence fixation of these foreign people in the eastern potiguar coast; discuss the sociocultural territorialization of the immigrants, as well as the plots of their social networks in Brazil and in their country of origin; comprehend the perception of the immigrants towards local public hospitality in the touristic and non-touristic territories; evaluate to what extent the migration has influenced the experiences of leisure of the researched ones. The study justifies itself mostly for being a thematic that requires theoretical deepening, facing the shortage of research in the Brazilian scenario, especially when it is considered the field of leisure studies. It is a complex study, of qualitative nature, that adopted as research strategies the case study and data collection by means of interview with 31 immigrants, natives of Italy, Spain and Portugal. The interpretative analysis was undertaken with the assistance of the software MAXQDA, seeking to organize and systematize the collected information with the interviewed. The results highlight that these subjects migrated searching for a new style of life and/or new personal challenges; for investing in the touristic and/or real estate sector, take over work functions and/or establish marital bonds. Regardless of the profile of the researched foreign people, it was realized that it is not about a merely material pursuit, but symbolic attached to the weather, sun, peace and nature presenting thus other matters that compose leisure. It was also highlighted that the coming of these immigrants has promoted the creation of new territorialities and territories, which was achieved by means of feeding, language, social networks, which have contributed with the process of adaptation and creation of new bonds. Regarding to social networks they form themselves in a very particular way, having a bigger approximation with Brazilians and estrangement of compatriots. The use of technology and social medias, however, was detached as fundamental in the maintenance of bonds left in the country of origin. It was verified that local public hospitality in the touristic territories is more present than in non-touristic territories, pointing to the inefficiency of the State, widely highlighted by immigrants. The research has recognized that one of the main consequences of migration was the expansion of leisure and a bigger fluidity in the work relations, making these two spheres of social life articulate instead of oppose. It was also perceived that on one hand, migration has facilitated the touristic experience of family and friends, and, on the other hand, it has allowed the circulation of these immigrants until the country of origin; pointing to the existence of an international flow. Lastly, migration was evaluated mostly as positive, having few interest in returning to the homeland. Thus, in this research international migration in the potiguar coast is an extension of the touristic phenomenon, having an influence on the incidence of new migratory and touristic flows, deflagrating thus its recursiveness.